Profiles about Events communication, study of shapes and techniques - Araibia, mohamed karim; nouari, Amel (Journal of Social Sciences and Humanities, 2021)
This research, which is titled : (Profiles on communication events , study in forms and techniques) one of the research belong to the science of Institutional communication, has dealt find definitions communication events to reach the scientific definition accurate, and functions that can be performed events communication, and forms display events communication on the audience in order to influence them and push them to conviction of the events and its contents . The department search to three sections are : First and titled (Nature of events communication ), and the second : titled ( Event functions and divisions ), and third : titled ( technique of events communication ) The events communication performs multiple function not limited to the marketing function, It is an informational function, economic function, social, and the function of entrainment, As the events communication, can be displayed in multiple ways, to ensure the desired effect to occur, including : events style influences, style drama, direct style of presentation, dancing and singing style .